Membangun Sistem Operasi Windows Serverless Mempermudah Pengembangan dan Deployment Aplikasi Modern - Rakhmadi Rahman; Nabilah Ramadhani Wowong; Fathin Alwan Tahir (International Forum of Researchers and Lecturers, 2024)
Exploring the concept of the Windows serverless operating system as a solution in the development and deployment of modern applications. Through a quantitative approach, this study evaluates how serverless technology can improve efficiency, reduce costs, and speed up the application development process. Using case studies and data analysis, this study provides practical guidance for developers and organizations in adopting serverless architectures in Windows environments.